Efeitos de um programa de caminhada orientada na qualidade de vida de mulheres adultas e idosas atendidas na atenção básica - Cerri, Natalia Caroline (2016)
Regular physical activity (PA) has the key role in the promotion of basic health benefits and, consequently, a good quality of life (QOL). The study evaluated the effect of a Program of Guided Walk (PGW) in relation to the QOL of adult and elderly women in high social vulnerability context, met in Primary Health Care (PHC) in São Carlos-SP, in the pre-intervention times, post-intervention and follow-up. It is a quasi-experimental study, not controlled, longitudinal and quantitative. For data collection characterization instruments of socio-demographic and economic aspects were used, the International Physical Activity Questionnaire (IPAQ) and WHOQOL-bref, which were filled through individual interviews with 28 participants. These made use of the accelerometer for four days in each evaluation period. For intra-group analysis, a descriptive analysis and data normality test were done; it has become necessary to use ANOVA for repeated measures and Friedman normal and non-normal data, respectively. In addition, it used the analysis by intention to treat (ITT). It was considered significant p<0.05. The average age of participants was 51.6 (DP± 14,8 years, in his married majority (67.9%), with education being one to eight years (53.6%) and less individual income or equal to the minimum wage (53.6%). In relation to the subjective levels of PA, participants doubled median with respect to the PA as a transport medium (p=0.035), and the PA domain Leisure (p=0.015), with significant differences in the studied periods. The objective analysis of PA levels of the participants showed an increase in counts for minutes (CPM), but no significant difference in three stages; and in relation to QOL levels, no significant differences were evaluated also. The physical domain showed marginally significant differences, with p=0.064. It is concluded that the extension of longitudinal studies are required to perform PA PHC interventions in vulnerable communities, by establishing a temporal relationship between the studied factors, and it may contribute to the development of more effective policies and programs.